2010
DOI: 10.1128/mcb.00157-10
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Deletion of Capn4 in Cells of the Chondrocyte Lineage Impairs Chondrocyte Proliferation and Differentiation

Abstract: Calpains are calcium-dependent intracellular cysteine proteases, which include ubiquitously expressed -and m-calpains. Both calpains are heterodimers consisting of a large catalytic subunit and a small regulatory subunit. The calpain small subunit encoded by the gene Capn4 directly binds to the intracellular C-terminal tail of the receptor for the parathyroid hormone (PTH) and PTH-related peptide and modulates cellular functions in cells of the osteoblast lineage in vitro and in vivo. To investigate a physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 53 publications
9
26
0
Order By: Relevance
“…Therefore, the functional changes of chondrocytes play an important role by contributing to the degradation of the articular cartilage and thus to the pathogenesis of OA (15,16). Several studies have reported that there is a very low proliferative activity in osteoarthritic chondrocytes, which might be an efficient treatment to cure or even delay the progression of OA by promoting chondrocyte proliferation (17,18). Therefore, the present study has focused on chondrocyte proliferation and extends the clinical observations of the potential anti-cartilage degenerative effect of millimeter waves and establishes a scientific foundation for further research.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the functional changes of chondrocytes play an important role by contributing to the degradation of the articular cartilage and thus to the pathogenesis of OA (15,16). Several studies have reported that there is a very low proliferative activity in osteoarthritic chondrocytes, which might be an efficient treatment to cure or even delay the progression of OA by promoting chondrocyte proliferation (17,18). Therefore, the present study has focused on chondrocyte proliferation and extends the clinical observations of the potential anti-cartilage degenerative effect of millimeter waves and establishes a scientific foundation for further research.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed reduced Akt phosphorylation and elevated PP2A levels in calpain 2-deficient AC2M2 cells, and this correlated with increased nuclear localization of FoxO3a and up-regulation of p27 Kip1 . Another recent study using conditional deletion of capns1 showed a role for calpain in embryonic chondrocyte proliferation (37). Disruption of calpain 1 and 2 in chondrocytes reduced cell cycle progression at G 1 /S transition, reduced cyclin D1 transcription, but enhanced the accumulation of cell cycle proteins cyclin D, cyclin E, and p27 Kip1 .…”
Section: Figure 6 Calpain 2 Regulates In Vivo P27mentioning
confidence: 97%
“…Changes in chondrocyte function are critical for the degradation of articular cartilage and serve an important function in the pathogenesis of OA (4,5). Several studies have reported that there is reduced proliferative activity in osteoarthritic chondrocytes and thus promoting chondrocyte proliferation may be an efficient strategy to treat or delay the progression of OA (6,7).…”
Section: Introductionmentioning
confidence: 99%